ExlA: A New Contributor to Pseudomonas aeruginosa Virulence - Huber, Philippe (Frontiers in Cellular and Infection Microbiology, 2022)
ExlA (also called Exolysin) is a recently-discovered virulence factor secreted by a subset of Pseudomonas aeruginosa strains, in which a type 3 secretion system is lacking. exlA-positive strains were identified worldwide in the clinic, causing several types of infectious diseases, and were detected in various locations in the environment. ExlA possesses a pore-forming activity and is cytolytic for most human cell types. It belongs to a class of poorly characterized bacterial toxins, sharing similar protein domain organization and a common secretion pathway. This review summarizes recent findings regarding ExlA synthesis, its secretion pathway and its toxic behavior for host cells.